2008
DOI: 10.1109/toh.2008.17
|View full text |Cite
|
Sign up to set email alerts
|

A Regression and Boundary-Crossing-Based Model for the Perception of Delayed Stiffness

Abstract: The stiffness of the environment with which we come in contact is the local derivative of a force field. The boundary of an elastic field is a singular region where local stiffness is ill-defined. We found that subjects interacting with delayed force fields tend to underestimate stiffness if they do not move across the boundary. In contrast, they tend to overestimate stiffness when they move across the elastic field boundary. We propose a unifying computational model of stiffness perception based on an active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
68
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 27 publications
6
68
2
Order By: Relevance
“…A springlike force field is a one-sided linear spring, i.e., a compression spring, in which an elastic force field is applied whenever the boundary of the field is crossed, namely, when the human operator created contact with the spring. We found that subjects overestimate stiffness when force lags position [34], but when the hand of subjects remained in continuous contact with the elastic force field they underestimated the delayed stiffness [35]. Moreover, we found a proximal-distal gradient in the amount of underestimation of delayed stiffness in the transition between probing with shoulder, elbow, and wrist joints [36].…”
Section: Preliminariesmentioning
confidence: 66%
“…A springlike force field is a one-sided linear spring, i.e., a compression spring, in which an elastic force field is applied whenever the boundary of the field is crossed, namely, when the human operator created contact with the spring. We found that subjects overestimate stiffness when force lags position [34], but when the hand of subjects remained in continuous contact with the elastic force field they underestimated the delayed stiffness [35]. Moreover, we found a proximal-distal gradient in the amount of underestimation of delayed stiffness in the transition between probing with shoulder, elbow, and wrist joints [36].…”
Section: Preliminariesmentioning
confidence: 66%
“…A general hypothesis supported by past work [11][12][13] is that time delays in position feedforward and haptic feedback can disturb the human operator and cause misjudgements. The key question we pose in this paper is how is the user performance of this basic manipulation task influenced by delays in haptic feedback?…”
Section: Introductionmentioning
confidence: 98%
“…Subjected to a forced-choice paradigm (i.e., distinguish the stiffer of two surfaces or identify them as having the same stiffness), users perceived the surfaces to be stiffer than actual under delayed force feedback and the stiffness overestimation increased for larger delays [11,12]. Recently, the effect of crossing the boundary of a force field, where local stiffness is ill-defined, on the perception of delayed stiffness has been studied [13]. It was found that subjects interacting with delayed force fields underestimate (overestimate) stiffness if they do not move (do move) across the boundary of the elastic field.…”
Section: Introductionmentioning
confidence: 99%
“…A general hypothesis supported by past work [12][13][14] is that time delays in position feedforward and haptic feedback can disturb the human operator and cause misjudgement. The key question we pose in this paper is, how is the performance of this basic manipulation task influenced by delays in haptic feedback?…”
Section: Introductionmentioning
confidence: 98%
“…Subjected to a forced-choice paradigm (i.e., distinguish the stiffer of the two surfaces or identify them as having the same stiffness), users perceived the surfaces to be stiffer than actual under delayed force feedback and the stiffness overestimation increased for larger delays [12,13]. Recently, the effect of crossing the boundary of a force field, where local stiffness is ill-defined, on the perception of delayed stiffness has been studied [14]. It was found that subjects interacting with delayed force fields underestimate (overestimate) stiffness if they do not move (do move) across the boundary of the elastic field.…”
Section: Introductionmentioning
confidence: 99%